Dialog Inter-Religius: Konsep Pengembangan Dakwah Pluralis - Umatin Fadilah (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2017)
This writing discusses about the inter-religious dialogue as propaganda pluralist concept development. Inter-religious dialogue is a dialogue between two or more religions, which has a different view and its main purpose is to learn each other so that they could have changed his view or add increased their religious experience. Inter-religious dialogue and develop the concept of religious experience that is no longer oriented propaganda that connotes coronation but mutually enrich and deepen their own experience of religious traditions.